2013
DOI: 10.1103/physreva.87.033404
|View full text |Cite
|
Sign up to set email alerts
|

Classical-trajectory simulation of accelerating neutral atoms with polarized intense laser pulses

Abstract: In the present paper, we perform the classical trajectory Monte Carlo simulation of the complex dynamics of accelerating neutral atoms with linearly or circularly polarized intense laser pulses. Our simulations involve the ion motion as well as the tunneling ionization and the scattering dynamics of valence electron in the combined Coulomb and electromagnetic fields, for both helium (He) and magnesium (Mg). We show that for He atoms, only linearly polarized lasers can effectively accelerate the atoms, while fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
(47 reference statements)
1
10
2
Order By: Relevance
“…For the case of ϕ = 0.5π, a smooth structure is obtained near the cut off area, and the cut off of the HHG extend to 205 eV, but the intensity is lower than the case of ϕ = 0. One of the difference with our previous work [13] is that the cut off extend for the case of ϕ = 0.5π, but the result shown in Ref. [13] (Fig.…”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…For the case of ϕ = 0.5π, a smooth structure is obtained near the cut off area, and the cut off of the HHG extend to 205 eV, but the intensity is lower than the case of ϕ = 0. One of the difference with our previous work [13] is that the cut off extend for the case of ϕ = 0.5π, but the result shown in Ref. [13] (Fig.…”
Section: Resultscontrasting
confidence: 72%
“…One of the difference with our previous work [13] is that the cut off extend for the case of ϕ = 0.5π, but the result shown in Ref. [13] (Fig. 2) is for the case of the wavelength equal 800 nm for the two circular pulses.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…It is well known that generation of isolated attosecond pulses is a manifestation of phase matching of just one-type of (i.e. either long or short, but not both) quantum paths in the supercontinuum regime [16,17]. Simultaneous superposition of both long and short quantum paths can destructively interfere with each other…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is surprised to find that, both theoretically [4] and experimentally [5], neutral atoms can survive strong laser fields in Rydberg states, known as Rydberg state excitation (RSE). Moreover, recent investigations have demonstrated that the RSE is closely connected to some interesting phenomena such as the absence of near-zeromomentum electrons [6] and the acceleration of neutral Rydberg atoms [7,8], and is also very useful in the enhancement of HHG [9]. Elaborate experimental and theoretical studies have been performed on this new strong-field phenomenon in the past few years [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%